1977
DOI: 10.1128/iai.18.2.549-551.1977
|View full text |Cite
|
Sign up to set email alerts
|

Physical changes in the epsilon prototoxin molecule of Clostridium perfringens during enzymatic activation

Abstract: Enzymatic activation of Clostridium perfringens epsilon prototoxin removed a small basic part of the molecule, causing a slight change in molecular weight (32,700 to 31,200) and a large change in isoelectric point (from pH 8.02 into fractions of 5.36 and 5.74).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 1 publication
2
22
0
Order By: Relevance
“…The molecular weight of mature epsilon-prototoxin calculated from the derived amino acid sequence (32,981) agreed with our experimentally determined value for the cloned and native proteins of 33,000. Previously, a range of molecular weights for the protein have been reported (from 23,200 to 40,500 [22]), although more recent estimates (29,45) are much closer to our value. The isoelectric points of epsilon-prototoxin and epsilontoxin have been reported to be 8.02 and 5.36, respectively (45).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The molecular weight of mature epsilon-prototoxin calculated from the derived amino acid sequence (32,981) agreed with our experimentally determined value for the cloned and native proteins of 33,000. Previously, a range of molecular weights for the protein have been reported (from 23,200 to 40,500 [22]), although more recent estimates (29,45) are much closer to our value. The isoelectric points of epsilon-prototoxin and epsilontoxin have been reported to be 8.02 and 5.36, respectively (45).…”
Section: Discussionsupporting
confidence: 84%
“…Previously, a range of molecular weights for the protein have been reported (from 23,200 to 40,500 [22]), although more recent estimates (29,45) are much closer to our value. The isoelectric points of epsilon-prototoxin and epsilontoxin have been reported to be 8.02 and 5.36, respectively (45). The estimated pIs of cloned prototoxin (8.35) and toxin (5.4) differ slightly from those of the previous reports but are identical to the major pIs of the purified proteins from C. perfringens type D, which we have determined.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Habeeb (9) reported the extensive purification of the prototoxin from culture supernatant fluid of the organisms. Some investigators have reported various physicochemical properties of epsilon prototoxin and epsilon toxin (1,10,11,13,21). On the other hand, it has been reported that the toxin increases vascular permeability in the brain and the intestine, as well as lethality and necrosis (2,3,7,8).…”
mentioning
confidence: 99%
“…perfringens epsilon toxin mediates lethal and necrotic activities. Habeeb [1,2] and Worthington et al [3] reported the physicochemical properties of the purified toxin. It also has been reported to increase vascular permeability in the brain [4] and the intestine [5] and to have pressor activity [6].…”
Section: Introductionmentioning
confidence: 99%